Mongol-Soviet Relations (1925-1928) - Batbayar Tsedendamba (Олон улс судлал, 2023)
The article explores the aspects of the interaction between Mongolia and the USSR on the development of their bilateral relations starting from 1925 up until 1928. The author shows how the Soviet troop withdrawal issue created by Moscow influenced the settlement of disputed issues between Mongolia and China, and interfered into the normalization Mongolian-Chinese relations for many years. Soviet envoy to the MPR P.M.Nikiforov was tasked to carry out total sovietazion of all aspects of Mongolian life under the nominal cover of independent Mongolia, and to prevent any process of unification between Outer and Inner Mongolia, to urge Mongolian leaders to recognize Tannu Tuva People’s Republic without any preconditions. A.Amar, Minister for Economy, during his trip to Moscow early 1926 raised the issues of distorted Mongol-Soviet trade, industrial, transport and other bilateral economic relations and asked Moscow to make adjustments and make economic relations equal and mutually beneficial. The character of the atmosphere between Ulaanbaatar and Moscow did play a key role in solving difficult and sensitive bilateral issues and the desire of the Mongolian People’s Republic to build official relations with Moscow as equal and trustful partners was strong.